Ru’yat al-aqallīyāt al-muslimah hawla al-tadayyun: Mawqif jayl al-shabāb fi Manado - Bukido, Rosdalina; Syarif, Ubed Abdilah; Mantu, Rahman (Studia Islamika, 2020)
This article presents data on the religious attitudes of Muslim minority communities. Similar themes have been studied considerably, but most of them are researched in the Muslim majority areas. Therefore, the author tries to delve into the same topic, but it investigates a different locus, namely how the religious views and attitudes of Muslim minority youth in Manado. The findings reveal that the attitudes and behavior of Muslim youth in Manado towards diversity tend to be conservative with scriptural and puritanical features. However, their basic attitude is highly open towards moderate values and principles, with a decent respect for individual freedom and human rights, even though norms and culture constrain them, this shows a paradox. On the one hand, they show a tolerant attitude, but on other certain aspects or problems, their attitude tends to be intolerant. In its context, the attitudes and religiosity of these Muslim youths have sparked social change in the City of Manado.